The Catholic internet television in thought theological of the Church - DOMASZK, ARKADIUSZ (Prawo Kanoniczne, 2018)
The article analyzed the Magisterium of the Catholic Church concerning means of communication, with a special focus on television. Subsequently, the Church teaching on the mass media in Poland was discussed, with a special reference to television. The discussion offered in this article constitutes the basis for the next part of the study which will examine the canonical norms related to television. The review of history and teaching of the Magisterium shows the particular transition: from initial aloofness towards new tools of communication, to positive acceptance. The Church was quite fast in recognizing television and using it in evangelization practice. Consequently, the pastoral application of television leads to using the influence of public and private stations as well as own Catholic television. A significant change in the post-Conciliar Church practice was including means of communication in pastoral programmers. The teaching of the Church is accompanied with statements and documents of particular Churches which are better adjusted to local ecclesiastic and media contexts. To sum up the teaching of the Church, one should say that it is not so much about establishing binding and strict norms as it is showing the direction and accompanying people and environments. Although the teaching of the Church does not discuss the thread of internet television development directly, this should be also referred to new forms of creating television transmission, including Catholic Internet viewers.